Cambridge Street-Names : Their Origins and Associations - Gray, Ronald D. (Cambridge University Press, 2000)
This book draws on the great wealth of associations of street-names in Cambridge. It is not a dictionary, but it provides a fascinating series of explanatory entries on historical periods and topics - and on a wide variety of notable and sometimes curious characters who lived in or often visited Cambridge.